Deep Cut Science, Power, and the Unbuilt Interoceanic Canal - Keiner, Christine (Since 1970: Histories of Contemporary America Ser., 2020)
HISTORY / Modern / 20th Century; SCIENCE / History; TECHNOLOGY & ENGINEERING / History